Biomechanical Study on Passing Technique Using Feet in Football Game; The Effect of Body Angle and Feet Position, Student of Sports Education Muhammadiyah University of East Kalimantan - Setiawan, Irfan Tri; Raharja , Andri Tria (FKIP - Universitas Riau, 2025)
Football is one of the most popular sports in the world and requires good basic technique mastery to achieve optimal performance. This study aims to analyze the effect of body angle and foot position on the effectiveness of the inside foot passing technique in football, and this study does not only aim to understand the theory behind the passing technique. This research method is a type of quantitative descriptive research with a survey data collection technique on the inside foot passing test and measurement. The instruments used are a cellphone camera for video capture, a laptop containing the kinovea 2023 1.1 application/software object 1 body angle of 144.5° there is a balance of load distribution between the two feet, the distance between the feet is 78.11 cm. Meanwhile, the body angle is 168.3° The distance between the feet is 109.19 cm which is too wide also has an impact on the lack of dynamic stability. These results support the findings of previous studies which state that optimal body posture, appropriate body angle, and stable distance between the feet can significantly increase passing accuracy.